A clinical case of severe disease burden: an erythrodermic psoriatic patient treated with secukinumab. (30th November 2018) - Galluzzo, M.; D'Adamio, S.; Campione, E.; Mazzilli, S.; Bianchi, L.; Talamonti, M.
Abstract: Erythrodermic psoriasis is a severe variant of psoriasis characterized by prominent erythema, affecting the entire body surface. Management of erythrodermic psoriasis is difficult, not standardized, and often ineffective. As clinical studies are lacking, reporting of clinical experience with secukinumab may help to gather insight into this field. Here, we describe the case of a 55-year-old man, with a 10-year history of moderate-to-severe plaque psoriasis. He presents a flare of erythroderma involving ∼90% of his body surface area and a psoriasis area and severity index score of 42, with an important impact on his quality of life (DLQI score was 20.0; Skindex-29 score was 67.2). The patient also presented alexithymic features. Due to the severity of clinical features and poor quality of life, the patient started secukinumab treatment; we observed a striking and rapid response to therapy with an excellent safety profile and a satisfactory compliance. Furthermore, therapy with secukinumab considerably enhanced patient's quality of life. Although further studies are needed to better understand the role of the IL-23/Th17 pathway, secukinumab can be an effective therapeutic option for patients affected by erythrodermic psoriasis.